Implementation of a Potential Information System to Improve Data Collection Efficiency at the Central Statistics Agency of Pidie Regency - Afkar, M. Khadafi (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2024)
The implementation of a new information system at the Central Statistics Agency (BPS) of Pidie Regency aimed to improve the efficiency of data processing, replacing the manual system that relied on Microsoft Word and Excel. The previous system led to delays, errors, and inefficiencies in generating reports. A new solution was developed using Microsoft Visual BASIC 6.0, addressing these issues by automating the data processing workflow. The development process included a feasibility study, system design, and coding, followed by thorough testing and staff training to ensure effective use of the system. The new system has successfully sped up data processing, reduced errors, and improved the accuracy of reports. This digital upgrade also enhanced transparency and accountability within BPS. The findings from this study demonstrate that the shift to automated information systems can significantly improve the operational efficiency of government agencies. The successful implementation of this system at BPS Pidie offers a potential model for other regions looking to modernize their data management processes.